Modern art, 1851-1929 - Brettell, Richard R. (Oxford University Press, 1999)
Richard R. Brettell's innovative and beautifully-illustrated account, the latest addition to the acclaimed Oxford History of Art series, explores the works of artists such as Monet, Gauguin, Picasso, and Dali--as well as lesser-known figures--in relation to expansion, colonialism, nationalism and internationalism, and the rise of the museum. Beginning with The Great Exhibition of 1851 in London, Brettell follows the development of the major European avant-garde groups: the Realists, Impressionists, Post-Impressionists, Symbolists, Cubists, and Surrealists...